Growth, physical fitness and specific motor skills in Portuguese young soccer players - Gaspar, H.; Almeida, M.-J.; Freitas, D.; Velosa, S.; Maia, J. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Young elite athletes are often a highly selected group, and in many sports they differ from the general population in somatic and motor characteristics (Malina and Bouchard, 1991). The main purpose of this study was to investigate differences in growth, physical fitness and specific motor skills in Portuguese soccer and non-soccer players. Methods The sample comprised 60 male subjects (30 soccer players and 30 non-soccer players) from 14 to 15 years of age. Soccer players engaged in a three training sessions per week (each one of 2 hours) in one of the best teams of Madeira (Portugal). Height, body mass, breaths, circumferences and skinfolds were measured using the same protocol as the Leuven Growth Study. Physical fitness was evaluated with the Eurofit test battery. Specific motor skills were assessed using the Portuguese Soccer Federation test battery. Statistical analysis was done using Intraclass Coefficient Correlation and the t-test. Significance was In field reliability was high for somatic (0.826<r<0.998), physical fitness (0.867<r<0.999) and specific motor skills (0.831<r<0.990) characteristics. Results No significant differences were found for height and body mass between groups. However, Soccer players showed higher mean values in some breaths (femur) and all circumferences (calf, thigh, upper arm, upper arm flexed, forearm and waist) than non-soccer players. In contrast, soccer players presented lower skinfolds (triceps, biceps, subscapular and suprailiac) than non-athletes. Also, in the physical fitness tests, soccer players showed a better performance in shuttle run, 12 minute walk-run, standing long jump, sit ups and flamingo balance. For specific motor skills (foot and head control, dribbling, passing, shooting and speed) soccer players present a better performance than their colleagues, except for the passing (Table 1). Discussion/Conclusion We conclude that regular soccer training is not associated with statural growth. However, the results suggest that youngsters engaging in regular soccer training have less subcutaneous fat and higher circumferences. It is well known that formal sport training has a positive impact in FFM (increase) and a favourable influence on FM (decrease). Differences in general motor abilities are significant between groups with soccer players presenting a better performance in nearly all specific motor skills. It means that guided instruction and adequate time of practice can induce to a better skill. Results from this study need to be interpreted with caution because of the small sample size, and we didn`t control for biological maturation and other potential sources of variation.